2006
DOI: 10.2164/jandrol.106.000109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Four Different Sperm Washing Methods Using Apoptotic Markers in Ram Spermatozoa

Abstract: The accurate measurement of semen fertilizing potential is of great importance in determining the acceptability of processed semen for breeding purposes. A good sperm preparation technique results in a sample with high viability and motility and also takes into account other parameters such as the capacitation and apoptotic state which could compromise the ability to fertilize an oocyte. In this study, we investigate the effects of 4 sperm preparation techniques (a dextran/swim-up procedure, discontinuous Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
5
31
0
Order By: Relevance
“…Because sperm motility is an indicator of cell viability, it is assumed that SU-processed sperm are of good quality. Some studies have demonstrated that membrane integrity and mitochondrial function are high, whereas DNA fragmentation and caspase expression decrease after SU processing (Sakkas et al, 2000;Martí et al, 2006Martí et al, , 2008Kotwicka et al, 2008). We evaluated in neat and SU samples cytoplasmic esterases and mitochondrial dehydrogenases as indicators of cytoplasmic membrane integrity and mitochondrial function by using calcein AM and resazurin, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because sperm motility is an indicator of cell viability, it is assumed that SU-processed sperm are of good quality. Some studies have demonstrated that membrane integrity and mitochondrial function are high, whereas DNA fragmentation and caspase expression decrease after SU processing (Sakkas et al, 2000;Martí et al, 2006Martí et al, , 2008Kotwicka et al, 2008). We evaluated in neat and SU samples cytoplasmic esterases and mitochondrial dehydrogenases as indicators of cytoplasmic membrane integrity and mitochondrial function by using calcein AM and resazurin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some ejaculated sperm express markers of apoptosis (Kotwicka et al, 2008;Martí et al, 2008), which are negatively correlated with semen quality (Weng et al, 2002;Almeida et al, 2005) and fertility (Fatehi et al, 2006). Using SU to sort sperm reduces the number of sperm expressing caspases (Martí et al, 2006(Martí et al, , 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis markers have been detected in spermatozoa of many species, but the role of these markers is probably not yet elucidated completely. 49,[119][120][121][122] Changes of sperm membrane permeability have been considered as a typical event of apoptosis in many studies. Since cryopreservation, freezing and thawing cause cryodamage, and presumably even apoptotic-like changes, 123 apoptotic markers can be good tools for forecasting semen freezability and cellular damage occur during cryopreservation, albeit not necessarily indicting apoptosis really occurs.…”
Section: Changes Induced During Capacitationmentioning
confidence: 99%
“…The investigations were performed in sperm derived from healthy male donors (Grunewald et al, in press), infertility patients (Brum et al, 2008;Martí et al, 2006) and animals (ram and equine spermatozoa) (Blanc-Layrac et al, 2000). In detail, double density gradient centrifugation is able to reduce the number of sperm showing caspase-3 activation to 15-20% in neat donor semen samples and to 43.5% in semen specimens from infertility patients.…”
Section: Potential Of Standard Spermmentioning
confidence: 99%